2001
DOI: 10.1038/sj.cgt.7700358
|View full text |Cite
|
Sign up to set email alerts
|

Selection of drug-resistant transduced cells with cytosine nucleoside analogs using the human cytidine deaminase gene

Abstract: Hematopoietic toxicity produced by most anticancer drugs limits their potential for curative therapy. We have shown previously that the human cytidine deaminase ( CD ) gene can confer drug resistance in murine bone marrow cells ( BMCs ) to the nucleoside analog, cytosine arabinoside ( ARA -C ) . In the present study, as the first objective we showed that the CD gene can also render drug resistance in BMCs to related analogs, 2 0 ,2 0 -difluorodeoxycytidine ( dFdC ) and 5 -azadeoxycytidine ( 5 -AZA -CdR ) . As … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 35 publications
(21 reference statements)
1
15
0
Order By: Relevance
“…This is in contrast to previous experiments performed with primary mononuclear murine bone marrow cells in which in vitro selection was prevented by the release of large amounts of CDD from CDD-transduced cells. 37 Therefore, another attractive application of CDD gene transfer may be the enrichment of genetically modified cells for gene therapy of monogenetic diseases. Here, selection strategies have been advocated for diseases caused predominantly by malfunction of hematopoietic cells in which the introduced therapeutic transgene does not confer a selective growth advantage to the transduced cells such as chronic granulomatous or Gaucher's disease.…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast to previous experiments performed with primary mononuclear murine bone marrow cells in which in vitro selection was prevented by the release of large amounts of CDD from CDD-transduced cells. 37 Therefore, another attractive application of CDD gene transfer may be the enrichment of genetically modified cells for gene therapy of monogenetic diseases. Here, selection strategies have been advocated for diseases caused predominantly by malfunction of hematopoietic cells in which the introduced therapeutic transgene does not confer a selective growth advantage to the transduced cells such as chronic granulomatous or Gaucher's disease.…”
Section: Discussionmentioning
confidence: 99%
“…Although self-renewal would be presumably be an integral part of this process, overtime preferential differentiation beyond normal hematopoietic limits may lead to extinction of the transduced stem-cell pool (Pollok, 2003). The expression of chemoprotective gene products such as the multidrug resistance protein (MDR1) (Abonour et al, 2000;Hanania et al, 1995;Hesdorffer et al, 1998;Hildinger et al, 1998;Schiedlmeier et al, 2000), dihydrofolate reductase (DHFR) (Allay et al, 1998;Brenner et al, 1993b;Corey et al, 1990;Persons et al, 2004;Warlick et al, 2002;Williams et al, 1987), cytidine deaminase gene (Beausejour et al, 2001;Eliopoulos et al, 2002;Momparler et al, 1996;Rattmann et al, 2006) and MGMT (Cai www.intechopen.com et al, 2008;Cai et al, 2006;Cai et al, 2005;Chinnasamy et al, 1998b;Davis et al, 2000;Davis et al, 1999;Hickson et al, 1998;Jansen et al, 2001;Jansen et al, 2002;Moritz et al, 1995;Neff et al, 2003;Ragg et al, 2000;Sawai et al, 2001) have been thoroughly investigated as potential candidates to protect hematopoietic cells residing in the bone marrow. A number of retroviral vectors derived from gamma-retroviruses, lentiviruses, and foamy viruses as described above continue to be tested for delivery of drug-resistance genes to primitive hematopoietic cells.…”
Section: Expression Of Drug-resistance Genes In Hspcsmentioning
confidence: 99%
“…This result was confirmed by others, both on fibroblasts and mouse bone marrow with araC, gemcitabine and 5-aza-deoxycytidine. [68][69][70][71][72] It was also shown that the resistance was reversed by using THU. 70 In the next step, transduced hematopoietic cells were transplanted into the bone marrow of mice to show the production of CDA in blood and different tissues.…”
Section: Myeloprotection With Cytidine Deaminasementioning
confidence: 99%
“…In vitro selection of transduced cells to select cells with high CDA expression before transplantation was easily obtained with murine leukemic L1210 cells and, although less easily, in murine bone marrow cells. 72 The selection was further applied to human peripheral and cord blood progenitor cells with araC and gemcitabine. 74 Finally, in vivo myeloprotection has been observed in mice treated with araC or gemcitabine after transplantation of CDAtransduced murine bone marrow cells.…”
Section: Myeloprotection With Cytidine Deaminasementioning
confidence: 99%